Electron-impact ionization of atomic ions in the Na isoelectronic sequence - YUMAK YAHŞİ, AYŞE; ALTUN, ZİKRİ (IOP PUBLISHING LTD, 2008)
Electron-impact ionization cross-sections and rate coefficients for the Na-like ions Mg+, Ar7+, Kr25+, Sn39+, Xe43+ and W63+ are presented. The direct ionization cross-sections of 2s, 2p and 3s subshells are calculated within a configuration-average distorted-wave (CADW) method. In addition, excitation-autoionization contributions originating from the inner-shell excitations of the type 2s22p63s -> 2s22p53snl (n = 3-6) and 2s22p63s -> 2s2p63snl (n = 3-6) are calculated using both CADW and level-resolved distorted-wave (LLDW) methods. We include the branching ratios for the radiation damping of the autoionizing configurations and levels. The excitation-autoionization contributions are found to be quite large for the lighter ions. For the heavier ions the radiation damping of the excitation-autoionization contribution is found to be significant. We find that the distorted-wave results are in good agreement with available experimental measurements, which only exist for Mg+, Ar7+ and Xe43+. We also find that the computationally simple configuration-average calculations are in reasonable agreement with the computationally demanding level-resolved calculations for the excitation-autoionization contributions for all the Na-like ions studied. In addition, Maxwellian rate coefficients are produced from our cross-sections and are archived in a format useful for plasma modelers.
Keywords: CROSS-SECTION MEASUREMENTS; FE-15+; MG; AUTOIONIZATION; AL2+; LI